KERJASAMA KONTRA-TERORISME ANTARA AUSTRALIA DENGAN INDONESIA DALAM MENANGGULANGI ANCAMAN TERORISME DI INDONESIA (2002-2008) - Hardiana, I Made Yuda; Sushanti, Suksma; Fasisaka, Idin (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACT Writer conducted this study has the purpose to describe the dynamics of counter-terrorism cooperation between Australia and Indonesia in tackling the threat of terrorism in Indonesia from 2002 to 2008 was a qualitative research study using the methods of literary study, internet, and print and electronic media. The first Bali bombing into the background between the two countries in counter-terrorism cooperation. That's because, first Bali bombing in the majority of the victims are Australian and Indonesia people. In this study it was found that the dynamics of counter-terrorism cooperation between the two countries look more closely with the signing of the Lombok Treaty as the legal basis of the two countries in the bilateral relations. The cooperation of these two countries forged reap positive results on the handling of terrorism cases in Indonesia. Cooperation can improve the capacity and capability as well as the role of the Indonesian police in exposing teorrism network in Indonesia. Keywords : terrorism, counter-terrorism cooperation, dynamics